Sistem Informasi Akuntansi Pelunasan BPIH Kantor Kementerian Agama Kabupaten Lumajang - Ika Nadia Choirunnisa; Sofiatul Magfiroh; Audilla Nurani Wijaya; Abdul Wadud Nafis (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
The BPIH repayment aims to cover the remaining shortfall in payment of Hajj Organizing Fees, which have been set by the government at IDR 55,928,458.26 for embarkation in East Java Province. Internal management of Hajj departures is carried out using the Integrated Hajj Computerized System. This research was conducted to determine the accounting information system for BPIH settlements in Lumajang Regency according to Minister of Religion Regulation No. 29 Tahin 2015. Data collection was carried out using interviews with Haj officers at the Ministry of Religion, Lumajang Regency, then the data was analyzed using qualitative methods. The research results show that the BPIH repayment system in Lumajang Regency has been implemented according to Minister of Religion Regulation No. 29 in 2015 and running optimally